Effects of folic acid on body folate status, ovarian function, and organ indexes of offspring during embryonic stage - Zhao, Jianfei; Lu, Zhongqian; Wu, Jialin; Zhu, Yufei (Frontiers in Veterinary Science, 2025)
This experiment aimed to investigate the effect of dietary folic acid supplementation on maternal folate status and ovarian function in female broiler breeders. Fifty 30-week-old Arbor Acres female broiler breeders were randomly divided into two groups (5 pens/group, 5 hens/pen) after 2 weeks of pre-feeding: the control group (Con, supplementation 0 mg/kg folic acid) and the folic acid group (FA, supplementation 4 mg/kg folic acid). The trial lasted 16 weeks. Folate content in eggs, maternal plasma, and offspring plasma (1-day-old) was measured, alongside expression levels of folate transporters in the ovary, liver, duodenum, and jejunum. Ovarian transcriptome analysis was performed. Results showed that the FA group had significantly increased folate deposition in eggs (p < 0.05) and offspring plasma folate levels (p < 0.01). No significant differences were observed in embryonic organ indexes (p > 0.05). The FA group had downregulated mRNA expression of proton-coupled folate transporter (PCFT) in the jejunum, folate transporter (RFC) in the liver, and folate receptors (FR) in the ovary (p < 0.05). However, they had upregulated RFC in the duodenum (p < 0.05). Transcriptome analysis identified 326 differentially expressed genes (217 up-regulated, 109 down-regulated; p < 0.05). KEGG enrichment revealed 10 pathways, including cell cycle, Wnt signaling, and steroid biosynthesis. These findings suggest that folic acid enhances ovarian reproductive gene expression and improves folate transfer to eggs and offspring.